The effect of teaching using the Internet Web on the first grade secondary students’ achievement in Physics and their attitudes towards it - Alosaimi, Ali Mutlaq (Journal of Educational and Psychological Sciences, 2020)
The current study aimed at investigating the effect of teaching using the Internet Web on the first grade secondary students’ achievement in Physics and their attitudes towards it.The experimental method was employed by using the two-group pre-post quasi-experimental design to answer the aforementioned questions. The sample consisted of (82) first grade secondary students enrolled in two sections which were randomly selected from all first grade secondary sections at Abhor educational complex in Jeddah province in the Kingdom of Saudi Arabia using the cluster random sampling technique, where the two sections were randomly assigned into the two groups. The students were distributed evenly by the two groups such as (41) students in each group, where the students in the experimental group were taught using the Internet, while the students in the control group were taught using the traditional method.For the purposes of data collection, two equivalent forms of an achievement test have been developed in order to measure the first three levels (remembering, understanding, and application) of the cognitive domain in the “movement representation” unit within the physics curriculum being taught to the first grade secondary school students in the academic year 2013/2014 H in the Kingdom of Saudi Arabia. Each form consisted of (35) multiple-choice questions with four alternatives. On the other hand, a pre-developed valid and reliable attitude scale towards physics in the Kingdom of Saudi Arabia was used.The results of the study revealed a statistically significant difference (α = 0.05) between the achievement post-test mean scores of the experimental and control groups for the favor of the experimental group who was taught using the educational site, which was designed and set up on the Internet Web. Similarly, the results revealed a statistically significant difference (α = 0.05) between the attitudes towards Physics post-test mean scores of both groups in favor of the experimental group.In light of the findings of the study, the researcher recommends conducting further studies on the benefits of using the Internet Web in the educational process in general and in distance learning in particular.
Keywords: The effect of teaching; the internet; achievement; physics; trends towards physics